The Existence of Regulatory Sandbox to Encourage the Growth of Financial Technology in Indonesia - Recca Ayu Hapsari; Maroni Maroni; Indah Satria; Nenni Dwi Ariyani (Universitas Lampung, 2019)
Bank Indonesia created an appropriate regulatory regime to drive the pace of innovation carried out by Financial Technology Providers while still applying the principles of consumer protection, risk management and prudence. One of the efforts made by Bank Indonesia was by issuing provisions concerning a regulatory sandbox for Financial Technology Providers along with their products, services, technology and/or business models in a Board of Governors Member Regulation No 19/14/PADG/2017 on the Limited Technology Testing Room (Regulatory Sandbox) Financial Technology. Meanwhile, the Financial Services Authority also issued regulation regarding the Regulatory Sandbox for Financial Technology Organizers in Financial Services Authority Regulation No. 13 / POJK.02/2018 on the Digital Financial Innovations in the Financial Services Sector. The main point of view to be analysed is the existence of regulatory sandbox approach held by Bank Indonesia and the Financial Services Authority as an effort to encourage the growth of Financial Technology in Indonesia.